Reproductive biology of catfish, Pachypterus atherinoides (Bloch, 1794) with Special Reference to lentic and lotic ecosystem - Angsuman Chanda; Godhuli Sit; Arun Jana (Aquatic Sciences and Engineering, 2024)
The study of reproductive biology is extremely crucial in fishery. Pachypterus atherinoides (Bloch, 1794) is a good food and ornamental catfish in the World. The present study aims to examine the seasonal reproductive behaviour of P. atherinoides in both lentic and lotic ecosystems. The study was conducted over two years in selected lentic and lotic aquatic ecosystems of the Jhargram and Paschim Medinipur districts of West Bengal, India: seasonally observed gonado-somatic index, fecundity and gonad maturation stages in both habitats in the study area. The study reveals that P. atherinoides shows single annual spawning and spawning during June to September. There is no significant difference between the breeding period between lentic and lotic aquatic ecosystems. This study would help aquaculturists in the culture, captive breeding, and conservation of P. atherinoides and also help researchers in the biometric study of another fish.